Molar Incisor Hypomineralization among School Children in Eastern Nepal: Prevalence, Clinical Patterns, and Predictors - Prajapati, Dilip; Ojha, Babita; Mahanta, Swagat K; Giri, Prapti; Pradhan, Darpa (Nepal Journal of Health Sciences, 2025)
Introduction: Molar Incisor Hypominerlization is notable condition that affects the enamel of first permanent molars, incisors and second deciduous molars, increasing sensitivity, dental decay risk and aesthetic concerns. Objective: This study aims to assess the prevalence and patterns of Molar Incisor Hypominerlization in children aged 6-12 years in schools within Phidim Municipality, Panchthar District, Nepal. Methods: An analytical, school-based study was conducted with 352 children aged 6- 12 years old students from Phidim Municipality. Ethical approval, parental consent and assent forms were obtained. Oral examinations guided by WHO Oral Health Assent Form (2013) and European Academy of Pediatric Dentistry criteria were conducted by a trained dental surgeon. Data were analyzed using IBM SPSS Statistics 25. Results: Molar Incisor Hypominerlization prevalence was 17.6% (62 children: 28 boys, 34 girls) where nine-year-old showed the highest prevalence (25.6%). Affected children with Molar Incisor Hypominerlization averaged 2.58 teeth per child, 2.11 affected molars and 1.76 affected incisors. Permanent first molars were most commonly affected (58.13%), followed by permanent incisors (27.5%). Mandibular molars were more frequently affected than maxillary molars (p < 0.05). No significant gender differences were observed. Molar Incisor Hypominerlization in deciduous molars were over 4 times likely to have it in their permanent molars with an OR = 4.9, 95% CI (1.74, 13.81); (15.1% versus 4.5%, respectively). Conclusion: School based oral health programs are a vital strategy for improving children’s access to dental care and reducing the burden of enamel defects.